Economies of Scope and Optimal Due Diligence in Corporate Acquisitions - Reuer, Jeffrey J.; Sakhartov, Arkadiy V. (Organization Science, 2021)
This study develops a theory of due diligence in corporate acquisitions. Using a formal model, the study situates due diligence in the context of economies of scope, which are often sought by acquiring organizations that have incomplete information about such economies. Relatedness, the key determinant of economies of scope, and ambiguity, the key determinant of incomplete information, are used to derive the optimal due diligence effort and the returns to an acquiring organization that result from that effort. The derived predictions qualify both the general appeal to extensive due diligence and the general recognition of the costliness of due diligence. These predictions can be tested in future empirical research on corporate acquisitions and may guide corporate acquirers on the optimal allocation of their due diligence efforts in the mergers and acquisitions market.